(untitled) (Italian Journal of Public Health, 2006)
Background Road traffic accidents represent an important public health problem in both industrialised and developing countries. In Italy, around 270,000 road traffic accidents occur annually. In 2001 this resulted in 6682 deaths, more than 20% of which were the result of an accident among users of two-wheeled motor vehicles [1].There is evidence that the raise in the speed limit [2] is associated with a sustained increase in traffic related deaths and case fatality rates. On 1st of July 2003 a new law was implemented,introducing new legal sanctions, the driver license points (after the experience in Germany, France, UK and Ireland, New Zealand and Brasil) [3,4], new speed limits and camera controls [5]. The aim of this study is to describe the differences in the epidemiological trend of road accidents in Italy, comparing data before and after the implementation of the new penalty points system law.